Pyogenic granuloma associated with mandibular odontoma. - Ocampo, Karla Gabriela; Díaz, Liliana; Barrera, José Luis (Journal of Oral Research; Vol 3 No 3 (2014)DO - 10.17126/joralres.2014.040, 2014)
Background: pyogenic granuloma is a kind of inflammatory hyperplasia of multifactorial origin, which is usually related to trauma or constant irritation, drug use, hormonal factors, among others. Meanwhile the odontoma is a benign tumor odontogenic composed of epithelial and mesenchymal cells, their development is usually associated with trauma, infections, inherited disorders or hyperactivity odontoblast. Objectives: The objective is to present the clinical case of a patient that presented a case of pyogenic granuloma related to the presence of a mandibular odontoma, and therapeutic management and postoperative results. Case report: The case shows a female patient of 32 years old with a history of multinodular goiter and hypothyroidism, developing a mandibular odontoma of the left side associated with pyogenic granuloma in the same area, which was treated with surgical excision and reconstructed affected tissues with lyophilized bone and collagen membrane. Favorable outcome after surgery without evidence of recurrence, with proper osseointegration of alloplastic materials and soft tissues. Conclusions: The irritant effect of the presence of a tumor (odontoma) in developing confirmed pyogenic granuloma. Keywords: pyogenic granuloma, odontoma, inflammatory hyperplasia. Granuloma piógeno asociado a odontoma mandibular. Caso clinico. Antecedentes: el granuloma piógeno es una especie de hiperplasia inflamatoria de origen multifactorial, que suele relacionarse a trauma o irritaciones constantes, uso de drogas, factores hormonales, entre otras. Por su parte el odontoma es una tumoración odontogénica benigna, compuesta de células epiteliales y mesenquimatosas, su desarrollo suele relacionarse con traumatismos, procesos infecciosos, alteraciones hereditarias o hiperactividad odontoblástica. Objetivos. El objetivo es presentar el caso clínico de una paciente la cual presento un caso de granuloma piógeno relacionado a la presencia de un odontoma mandibular; así como el manejo terapéutico y los resultados posoperatorios. Caso clínico: El caso muestra a una paciente del sexo femenino de 32 años de edad con antecedentes de bocio multinodular e hipotiroidismo, desarrollando un granuloma piógeno asociado al desarrollo de un odontoma mandibular del lado izquierdo, el cual fue tratado con extirpación quirúrgica y los tejidos incidido reconstruidos con hueso liofilizado y membrana de colágeno. Evolución favorable pos quirúrgica, sin evidencia de recidiva, con correcta osteointegración de materiales aloplásticos y tejidos blandos. Conclusiones: se confirma el efecto irritante de la presencia de una tumoración (odontoma) en el desarrollo de un granuloma piógeno. Palabras clave: Granuloma piógeno,  odontoma, hiperplasia inflamatoria.